An unattended silent killer: A facility-based cross-sectional study on undiagnosed hypertension from Haryana, India - Vijay Kumar Silan; Ramesh Kumar Verma; Ravinder Pal; Tarun (Asian Journal of Medical Sciences, 2022)
Background: Non-communicable diseases are on the upsurge throughout the world. They take a toll of 71% of overall total death, majorly contributed by cardiovascular disease. Hypertension has been a consistent risk factor for cardiovascular diseases among the various risk factors. Hypertension’s asymptomatic nature makes it a silent killer; many lives are avertable if a timely diagnosis can be assured. Aims and Objectives: The aim of this study was to determine the prevalence of undiagnosed hypertension among the attendees of a sub-district hospital. Materials and Methods: We conveniently chose 100 participants of age 30 years from the out-patient department of a sub-district hospital in Gohana, Haryana. Any attendees aged more than 30 years was requested to participate in the study. The execution of the study was done in accordance to the guidelines laid in Helsinki Declaration 1975, revised 1983. Due permission was taken from the concerned authority of the study facility. After obtaining well-informed consent, data were collected through a semi-structured questionnaire. The blood pressure was measured and classified per JNC-8 guidelines. Any participant having systolic B.P. more than 140 mmHg and diastolic B.P. more than 90 mmHg on two 5 min apart readings was considered hypertensive. The descriptive analysis was done in terms of frequencies and proportions. The Chi-square test was done to determine any association of undiagnosed hypertension with selected risk factors. Results: We report a 59% prevalence of undiagnosed hypertension among study participants. The undiagnosed hypertension was statistically associated (P<0.05) with higher body mass index, less physically active, being a diabetic, alcoholic, smoker, and having a positive family history of hypertension. Only 2% of the participants knew of any health program on non-communicable diseases. Conclusion: A higher prevalence of undiagnosed hypertension even after health facility visits for any other reason warrants the standardized and universal blood pressure measurement of patients visiting health facilities irrespective of the health issue, for which they are visiting.